A department of social and preventive medicine in a district general hospital. Issue 539 (September 1970) - McQuillan, W. J.; Williams, B. T.
Abstract : The Bonham-Carter Report on the Functions of the District General Hospital favoured the idea of locating a department or office of the local health authority at the district general hospital, in order to help in achieving functional integration of the hospital and community health services. This paper describes the establishment and development of such a department in a district general hospital, outlines its functions and describes some of the projects undertaken.